Maternal health posts shared on Instagram: a content analysis of popular birthing and parenting accounts - George, Nerissa; de Long, Rachel; Ahmed, Rukhsana; Kacica, Marilyn; Manganello, Jennifer A. (Frontiers in Communication, 2023)
Recent studies have found that maternal health knowledge gaps exist amongst Black women, especially related to postpartum complications. The prenatal period is a key time when pregnant women have direct access to evidence-based sources such as healthcare providers to obtain maternal health and pregnancy information. Yet, Black pregnant women are also more likely to forgo or engage in prenatal care later than their White counterparts. In recent years, social media have become an essential source of pregnancy-related information and have been shown to effectively improve pregnancy knowledge. Social media have the potential to inform pregnant women about important pregnancy and postpartum health information. Yet, no studies to date have explored the type of maternal health content Black women are exposed to on popular pregnancy and parenting Instagram accounts. This content analysis sought to identify what pregnancy topics appear and whether diverse birthing women representation exists on Instagram accounts popular among birthing women. Instagram posts from three social media accounts commonly used for pregnancy and parenting information from 5/1/18 to 4/30/21 were collected and then screened for maternal health content. A total of 212 maternal health posts were identified. Maternal health content represented 5% (219 out of 4,572 posts) of all posts shared by all accounts. About 35% (69 out of 196) of the images shared on all of the accounts included people but lacked diversity. These results highlight significant missed opportunities to share maternal health and Black maternal health content to educate and promote diversity among women who utilize these popular parenting Instagram accounts. Social media can be a viable and innovative solution to help create and promote maternal health information equity.